2019
DOI: 10.1183/23120541.00135-2019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of transbronchial cryobiopsy in eccentrically and adjacently orientated radial endobronchial ultrasound lesions

Abstract: BackgroundRadial endobronchial ultrasound (R-EBUS) is an effective technique in the diagnosis of peripheral pulmonary lesions (PPL). However, lesion orientation with regards to the radial probe remains an important factor for effective biopsy. “Within” orientation was associated with significantly higher diagnostic yield. Cryobiopsy is a novel technique in obtaining larger tissue samples with the frozen tip allowing biopsy in a 360° direction, thus potentially achieving more effective biopsy in eccentrically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 22 publications
4
65
1
1
Order By: Relevance
“…Transbronchial cryobiopsy (TBCB) is widely used in the diagnosis of diffuse parenchymal lung disease (DPLD), the use of which has been standardized through expert recommendations [7]. However, its role in SPN diagnosis remains uncertain although various studies have demonstrated its feasibility, especially if lesions are eccentric or adjacently orientated to rEBUS [4,8]. However, the conventional cryoprobe is stiff and may not be easily inserted into all regions of the lung, especially in highly angulated bronchi such as the apical segment of the upper and lower lobe [5].…”
Section: Discussionmentioning
confidence: 99%
“…Transbronchial cryobiopsy (TBCB) is widely used in the diagnosis of diffuse parenchymal lung disease (DPLD), the use of which has been standardized through expert recommendations [7]. However, its role in SPN diagnosis remains uncertain although various studies have demonstrated its feasibility, especially if lesions are eccentric or adjacently orientated to rEBUS [4,8]. However, the conventional cryoprobe is stiff and may not be easily inserted into all regions of the lung, especially in highly angulated bronchi such as the apical segment of the upper and lower lobe [5].…”
Section: Discussionmentioning
confidence: 99%
“…4,10 As opposed to conventional forceps, which only allow forward sampling, cryoprobe can obtain tissue in a 360 o manner laterally. 24 Similarly, in the experience with Case 4, nodules that were tangentially oriented despite having the pleuroscope at maximal angulation were much easier to sample with cryoprobe than conventional forceps. Third, in terms of technical difficulty, there is no significant difference in operator-rated difficulty when comparing cryobiopsy to conventional forceps technique; 12 this is promising and may encourage more pulmonologists to adopt it in the future, although studies on its learning curve are lacking.…”
Section: Discussionmentioning
confidence: 96%
“…Conventional cryoprobe was thick and straight and limited to large bronchus. Hemorrhage is also a considerable problem and it induced more bleeding than forceps [15,[25][26][27]. Usually, the conventional cryoprobe need to be withdrawn with bronchoscope after biopsy, leaving the airway out of surveillance, so an additional insertion of a bronchoscope is required immediately after the former bronchoscope retreated [28].…”
Section: Discussionmentioning
confidence: 99%